2020
DOI: 10.1371/journal.pone.0235568
|View full text |Cite
|
Sign up to set email alerts
|

Undefeated—Changing the phenamacril scaffold is not enough to beat resistant Fusarium

Abstract: Filamentous fungi belonging to the genus Fusarium are notorious plant-pathogens that infect, damage and contaminate a wide variety of important crops. Phenamacril is the first member of a novel class of single-site acting cyanoacrylate fungicides which has proven highly effective against important members of the genus Fusarium. However, the recent emergence of field-resistant strains exhibiting qualitative resistance poses a major obstacle for the continued use of phenamacril. In this study, we synthesized nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Because the cyano group of phenamacril does not form any discernible interaction with FgMyo1 except for the nonessential hydrogen bond with the S217 OH group, we propose the cyano group of phenamacril as a key modification site for the development of novel fungicides. Wollenberg et al recently showed that substitution of the cyano group of phenamacril with an ethyl ester completely abolishes the fungicidal activity and the inhibition of FgMyo1 ATPase activity . This is likely caused by the steric hindrance of the ethyl ester, which is much bulkier than the cyano group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Because the cyano group of phenamacril does not form any discernible interaction with FgMyo1 except for the nonessential hydrogen bond with the S217 OH group, we propose the cyano group of phenamacril as a key modification site for the development of novel fungicides. Wollenberg et al recently showed that substitution of the cyano group of phenamacril with an ethyl ester completely abolishes the fungicidal activity and the inhibition of FgMyo1 ATPase activity . This is likely caused by the steric hindrance of the ethyl ester, which is much bulkier than the cyano group.…”
Section: Discussionsupporting
confidence: 89%
“…Wollenberg et al recently showed that substitution of the cyano group of phenamacril with an ethyl ester completely abolishes the fungicidal activity and the inhibition of FgMyo1 ATPase activity. 25 This is likely caused by the steric hindrance of the ethyl ester, which is much bulkier than the cyano group. We expect that phenamacril analogues with smaller substituents in place of the cyano group might retain the fungicidal activity.…”
Section: Discussionmentioning
confidence: 99%